Assessment of the in vitro Efficacy of the Novel Antimicrobial Peptide CECT7121 against Human Gram-Positive Bacteria from Serious Infections Refractory to Treatment - Sparo, Mónica Delfina (2009)
Background: Resistant Gram-positive bacteria are causing increasing concern in clinical practice. This work investigated theefficacy of AP-CECT7121 (an antimicrobial peptide isolated from an environmental strain of Enterococcus faecalis CECT7121) against various pathogenic Gram-positive bacteria. Methods: Strains were isolated from intensive care unit patients unresponsive to standard antibiotic treatments. Inhibitory activity of AP-CECT7121 was assessed using the agar-well diffusion method. The most resistant isolates from each species screened (Enterococcus faecium, Enterococcus faecalis,Staphylococcus aureus, Streptococcus pneumoniae, Streptococcus pyogenes, Clostridium perfringens and Clostridium difficile) were further examined in time-killing curve studies. Results: These bactericidal kinetic experiments demonstrated a rapid killing effect with no viable bacteria being detected within 30 and 90 min for enterococcal and streptococcal strains and 180 min for community-acquired methicillin-resistant S. aureus and C. perfringens: viable counts for C. difficile were threefold decreased after 90 min. Conclusions: AP-CECT7121 may provide a novel strategy for treating potentially fatal clinical infections in hospitalized patients.